Caregiver Global Impression Observations from EMBARK: A Phase 3 Study Evaluating Delandistrogene Moxeparvovec in Ambulatory Patients with Duchenne Muscular Dystrophy - Craig M. McDonald; Jacob S. Elkins; Sai Dharmarajan; Katherine Gooch; Teofil Ciobanu; Claire J. Lansdall; Alexander P. Murphy; Fiona McDougall; Eugenio M. Mercuri; Ivana Audhya; the EMBARK Study Group (Neurology and Therapy)
Abstract Introduction Duchenne muscular dystrophy (DMD) is a rare, progressive, debilitating neuromuscular disease. The early childhood onset and debilitating nature of the disease necessitate decades of caretaking for most patients. Caregivers have a critical role in evaluating patients’ physical functioning and/or response to treatment. Using DMD-specific caregiver-reported scales, the impact of delandistrogene moxeparvovec gene therapy on caregivers’ perceived change in patient disease status or severity was evaluated using the Caregiver Global Impression of Change and Severity (CaGI-C and CaGI-S, respectively). Methods In the Phase 3 randomized, double-blind, placebo-controlled trial (EMBARK; NCT05096221), the CaGI-C at week 52 and change from baseline to week 52 in CaGI-S were evaluated in a post hoc analysis. The CaGI-C assesses caregivers’ impressions of change in DMD symptoms, physical ability, ability to perform daily activities, and overall health. The CaGI-S evaluates current severity of DMD symptoms, physical ability, ability to perform activities of daily living, and overall health. Data were evaluated using multi-domain responder index (MDRI) and ordinal regression analyses. Results MDRI analyses across all four CaGI-C items yielded a treatment difference of 1.7 (95% confidence interval [CI]: 0.90–2.5) favoring delandistrogene moxeparvovec; a treatment difference of 1.1 (95% CI 0.30–1.9) was observed for the CaGI-S favoring delandistrogene moxeparvovec. After adjusting for age, ordinal regression analysis showed a nominally significant increase in the odds of achieving a better rating for delandistrogene moxeparvovec-treated patients on all four CaGI-C items (≥ 3.8-fold increase). After adjusting for baseline severity and age, ordinal regression analysis showed a nominally significant increase in the odds of improvement on all four CaGI-S items (≥ 2.2-fold increase). Conclusion These exploratory findings captured by caregiver-reported outcomes add to the totality of evidence that supports the clinical benefits of delandistrogene moxeparvovec for patients with DMD. Trial Registration Number ClinicalTrials.gov identifier, NCT05096221.